End of Life Planning and its Relevance for Patients and Oncologists’ Decisions in Choosing Cancer Therapy - Saraiya, Biren (2008)
The goal of end of life (EoL) planning is to provide individuals with tools to control their financial and health care decisions when they are incapacitated. When an elderly patient is diagnosed with advanced cancer, the possible treatment options are: palliative care with curative intent or prolongation of life or palliative care only. Treatment of cancer in elderly patients creates a significant array of monetary and symptom burdens. The question is whether advance care planning (ACP), part of EoL planning, allows patients families and communities to control and reduce these burdens. Although the number of patients completing advance directives has increased in recent years, there are multiple barriers to the implementation of patients’ wishes such as limited knowledge of patient wishes by proxy and physician and inadequate communication regarding prognosis. We propose that improvements in patient decision making and clinical practice can reduce the burden of symptoms for patients if clinicians better understood patients’ models and expectations respecting the longer term consequences of diagnosis and treatment. This understanding can arise from improved information exchange and constant updating of the information as the disease and treatment evolves. Clinicians also need better prognostication tools and better training in effective communication skills to elicit patient goals and make appropriate recommendations.